Abscisic Acid Flux Alterations Result in Differential Abscisic Acid Signaling Responses and Impact Assimilation Efficiency in Barley under Terminal Drought Stress . Issue 4 (7th March 2014) - Seiler, Christiane; Harshavardhan, Vokkaliga T.; Reddy, Palakolanu S.; Hensel, Götz; Kumlehn, Jochen; Eschen-Lippold, Lennart; Rajesh, Kalladan; Korzun, Viktor; Wobus, Ulrich; Lee, Justin; Selvaraj, Gopalan; Sreenivasulu, Nese
Abstract : ABA homeostasis achieved in the tolerant lines is closely coupled to readjustment in ABA receptors, which enables this line to maintain a favorable WUE and photoassimilate accumulation when challenged by terminal drought . Abstract: Abscisic acid (ABA ) is a central player in plant responses to drought stress. How variable levels of ABA under short-term versus long-term drought stress impact assimilation and growth in crops is unclear. We addressed this through comparative analysis, using two elite breeding lines of barley ( Hordeum vulgare ) that show senescence or stay-green phenotype under terminal drought stress and by making use of transgenic barley lines that express Arabidopsis ( Arabidopsis thaliana ) 9-cis-epoxycarotenoid dioxygenase ( AtNCED6 ) coding sequence or an RNA interference (RNAi) sequence of ABA 8′-hydroxylase under the control of a drought-inducible barley promoter. The high levels of ABA and its catabolites in the senescing breeding line under long-term stress were detrimental for assimilate productivity, whereas these levels were not perturbed in the stay-green type that performed better. In transgenic barley, drought-inducible AtNCED expression afforded temporal control in ABA levels such that the ABA levels rose sooner than in wild-type plants but also subsided, unlike as in the wild type, to near-basal levels upon prolonged stress treatment due to down-regulation of endogenous HvNCED genes. Suppressing of ABA catabolism with the RNA interference approach of ABA 8′-hydroxylase caused ABA flux during the entire period of stress. These transgenic plants performed better than the wild type under stress to maintain a favorable instantaneous water use efficiency and better assimilation. Gene expression analysis, protein structural modeling, and protein-protein interaction analyses of the members of the PYRABACTIN RESISTANCE1/PYRABACTIN RESISTANCE1-LIKE/REGULATORY COMPONENT OF ABA RECEPTORS, TYPE 2C PROTEIN PHOSPHATASE Sucrose non-fermenting1-related protein kinase2, and ABA-INSENSITIVE5/ABA-responsive element binding factor family identified specific members that could potentially impact ABA metabolism and stress adaptation in barley.